Incidence of incisional hernia with respect to different sites and causes - Chavan, Shahaji G.; Nithin, Saladi Naga; Jaiswal, Karan; Rambatla, Manasa (International Surgery Journal, 2020)
Background: Of all hernias encountered, incisional hernias can be the most frustrating and difficult to treat. The aim of this study is to find out the incidence of incisional hernia at different sites and to find out their possible causes. Methods: This was a prospective study of 50 cases of Incisional hernias admitted during the period between July 2017 to July 2019. Collected data is analysed over a period of 3 months. Patients with Incisional hernia satisfying the inclusion criteria, attending surgery OPD at Dr. D. Y. Patil Medical College, Pimpri, Pune were included in study group. Results: Mean age at presentation was 45 (32/50) were female 18 patients were male. Majority of the patients were obese. Infra-umbilical variety of incisional hernia is most common 42%. The most common primary surgery is tubal ligation was 14 (28%). Significant association noted between diabetes mellitus and SSI, p value <0.05. There is a significant association between addictions (tobacco, smoking and alcohol) and hernias in umbilical region and above p value <0.005. Conclusions: The incidence of incisional hernia is more in multiparous females. Infra-umbilical midline was the most common site for herniation in 42% of cases. Lower midline incisions are more prone for herniation as the posterior rectus sheath is deficient below arcuate line. The most common previous surgery was tubectomy 14. Diabetes and SSI played important role in causing incisional hernia in our study.